Gut commensal microbes do not represent a dominant antigenic source for continuous CD4+ T‐cell activation during HIV‐1 infection. Issue 11 (23rd October 2015) - Zimmermann, Kathrin; Bastidas, Sonia; Knecht, Leandra; Kuster, Herbert; Vavricka, Stephan R.; Günthard, Huldrych F.; Oxenius, Annette
Abstract : Chronic immune activation is a hallmark of HIV‐1 infection; specifically, the activation of T cells has predictive value for progression to AIDS. The majority of hyperactivated T cells are not HIV‐specific and their antigenic specificities remain poorly understood. Translocation of gut luminal microbial products to systemic sites contributes to chronic immune activation during HIV‐1 infection, but how it affects (TCR‐dependent) immune activation remains elusive. We hypothesized that gut luminal antigens foster activation of CD4 + T cells with specificities for commensal bacterial antigens, thereby contributing to the pool of activated CD4 + T cells in the circulation of HIV‐1 infected individuals. To test this hypothesis, we quantified the frequencies of gut microbe‐specific CD4 + T cells by cytokine production upon restimulation with selected gut commensal microbial antigens. Contrary to our hypothesis, we did not observe increased but rather decreased frequencies of gut microbe‐specific CD4 + T cells in HIV‐1 infected individuals compared to healthy controls. We conclude that the increased activation status of circulating CD4 + T cells in HIV‐1 infected individuals is not driven by CD4 + T cells with specificities for commensal bacterial antigens.